2010
DOI: 10.1007/s10585-009-9303-6
|View full text |Cite
|
Sign up to set email alerts
|

Protease inhibitor SERPINA1 expression in epithelial ovarian cancer

Abstract: Epithelial ovarian cancer is the most lethal gynecologic cancer with a 5 years survival rate of 30-40% in patients diagnosed with high-grade invasive disease (TOV). This is in stark contrast to the 95% 5 years survival rate in ovarian cancer patients diagnosed with low malignant potential (LMP) disease. The progression from localized tumor to invasive metastasis involves matrix proteolysis. Protease inhibitors are thought to play a key role by limiting this process. Using the Affymetrix HG-U133A GeneChip array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 63 publications
4
23
1
Order By: Relevance
“…These findings suggest that serpinA1 affects the incidence and progression of gastric cancer by promoting the mobility and metastasis of cancer cells. Our results are in concordance with other studies, which reported that serpinA1 has a role in tumour progression (Tahara et al , 1984; Karashima et al , 1990; Higashiyama et al , 1992; Allgayer et al , 1998; de Sá et al , 2007; Normandin et al , 2010; Farshchian et al , 2011). …”
Section: Discussionsupporting
confidence: 94%
“…These findings suggest that serpinA1 affects the incidence and progression of gastric cancer by promoting the mobility and metastasis of cancer cells. Our results are in concordance with other studies, which reported that serpinA1 has a role in tumour progression (Tahara et al , 1984; Karashima et al , 1990; Higashiyama et al , 1992; Allgayer et al , 1998; de Sá et al , 2007; Normandin et al , 2010; Farshchian et al , 2011). …”
Section: Discussionsupporting
confidence: 94%
“…SERPINA1 shows one of the largest fold increases (3.8-fold increased) in protein expression level in PTR cohort compared with PTS cohort (p<0.05). Nevertheless, our data are in good agreement with prior studies elicited above, but disagree with the results of Normandin et al (7).…”
Section: Discussionsupporting
confidence: 76%
“…In the oncology literature reports describe genetic aberrations in cancer, 22 increased levels in the serum of patients with cancer 23 and a survival disadvantage for tumors expressing A1AT. 24 Previously, we reported that A1AT has 74% sensitivity and 80% specificity, 9 which are slightly decreased from current findings (87% and 84%, respectively). We believe that this difference is due to 1) different ELISA kits used to detect A1AT and 2) different statistical analyses.…”
Section: Discussioncontrasting
confidence: 65%